2001
DOI: 10.1590/s0034-71082001000200010
|View full text |Cite
|
Sign up to set email alerts
|

Microbial respiration and chemical composition of different sediment fractions in waterbodies of the upper Paraná River floodplain, Brazil

Abstract: Four size fractions of the sediment of six environments of the upper Paraná River floodplain were analyzed for carbon, nitrogen, and phosphorus contents and microbial respiration (oxygen consumption). Particle size did not affect nitrogen and phosphorus content or microbial activity, but did affect carbon content (F = 4.274, df = 3; 20, p = 0.020). The carbon concentration of ultra-fine particles was significantly lower than that of other sizes of sediment particles. Microbial respiration values were well pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Most studies of the C cycle in rivers were conducted in pristine and disturbed watersheds in temperate regions (e.g., Yang et al 1996;Jarvie et al 1997;Amiotte-Suchet et al 1999;Aucour et al1999;Telmer and Veizer, 1999;Abril et al 2000; Wang and Veizer 2000;Helie et al 2002;Dawson et al 2001; Barth et al 2003;Finlay 2003;Raymond and Cole 2003) or in the largest and most pristine watersheds of the tropics (Devol et al 1987;Richey et al 1990;Quay et al 1992;Hamilton et al 1997;Galy and France-Lanord 1999;Thomaz et al 2001;Richey et al 2002). Much less attention has been devoted to smaller disturbed and undisturbed watersheds in the subtropics or tropical regions (Ballester et al 1999;Andrews et al 1998;Das et al 2005;Stephens and Rose, 2005;Jepsen and Winemiller 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the C cycle in rivers were conducted in pristine and disturbed watersheds in temperate regions (e.g., Yang et al 1996;Jarvie et al 1997;Amiotte-Suchet et al 1999;Aucour et al1999;Telmer and Veizer, 1999;Abril et al 2000; Wang and Veizer 2000;Helie et al 2002;Dawson et al 2001; Barth et al 2003;Finlay 2003;Raymond and Cole 2003) or in the largest and most pristine watersheds of the tropics (Devol et al 1987;Richey et al 1990;Quay et al 1992;Hamilton et al 1997;Galy and France-Lanord 1999;Thomaz et al 2001;Richey et al 2002). Much less attention has been devoted to smaller disturbed and undisturbed watersheds in the subtropics or tropical regions (Ballester et al 1999;Andrews et al 1998;Das et al 2005;Stephens and Rose, 2005;Jepsen and Winemiller 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Santmire and Leff (2006) found no difference in the bacterial community composition among different sediment fractions indicating that in their case, functioning rather than structure underlies these differences. Also, Thomaz et al (2001) found no correlation between particle size and microbial respiration in waterbodies of the upper Paraná River floodplain but did recognize the phosphorus contents as important variable. In contrast to our study, their study compared fine sediments, with four sediment classes of sizes below 0.070 mm.…”
Section: Discussionmentioning
confidence: 76%
“…We observed a significant temporal influence of SIM on the abundance of exogenous testate amoebae. Thomaz, Pereira, & Pagioro, suggested that the direct or indirect influence of suspended inorganic material on the distribution of organisms may be more explicit in floodplain environments, where its availability is controlled by the hydrological regime.…”
Section: Discussionmentioning
confidence: 99%